IMPLEMENTATION OF HIGHER ORDER THINKING SKILLS (HOTS)-BASED EDUCATION TO ENHANCE THE QUALITY OF ENGLISH LANGUAGE FOR STUDENTS AT SDN 1 TIMPAG - Utik Kuntariati; Putu Dian Yuliani Paramita; Gede Eka Wahyu (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This study focuses on the implementation of Higher Order Thinking Skills (HOTS) in English learning to prepare students for the demands of Education 4.0, which aims to produce competent and high-quality human resources capable of performing effectively in the industrial world (Pohan, 2019). In today’s education, students are required to process broad information and develop understanding in various fields, including English. The research employed a qualitative descriptive method, which emphasizes describing phenomena using words rather than numbers. The study was conducted at SDN 1 Timpag. Based on the results, it was concluded that the HOTS learning indicators are developed comprehensively, encompassing six aspects: Creating, Evaluating, Analyzing, Applying, Remembering, and Understanding. However, there are areas for improvement in implementing HOTS in English learning, such as in storytelling planning, introducing animal objects and body anatomy, using simple greetings, and applying grammar.